2020
DOI: 10.1111/jsr.13047
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perinatal depression and infant sleep problems at 1 year of age: Subjective and actigraphy data from a population‐based birth cohort study

Abstract: Maternal perinatal depression, defined as an episode of major depression occurring from pregnancy to the first 12 months after delivery, is a highly prevalent condition, affecting up to 20% of childbearing women (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
(66 reference statements)
0
16
1
Order By: Relevance
“…Third, because the study was framed around mothers’ and infants’ sleep, the number of women with mood disturbances may be overrepresented relative to the general population because participants experiencing sleep problems and infant sleep problems may have been more likely to complete the survey. Only 30% of our sample indicated an absence of infant sleep problems as compared to 75-88% in other samples [ 91 , 92 ] . Fourth, we did not employ objective measures for assessing sleep problems (e.g., actigraphy) or use a clinical interview for establishing the presence of depressive disorders for participants.…”
Section: Discussioncontrasting
confidence: 76%
“…Third, because the study was framed around mothers’ and infants’ sleep, the number of women with mood disturbances may be overrepresented relative to the general population because participants experiencing sleep problems and infant sleep problems may have been more likely to complete the survey. Only 30% of our sample indicated an absence of infant sleep problems as compared to 75-88% in other samples [ 91 , 92 ] . Fourth, we did not employ objective measures for assessing sleep problems (e.g., actigraphy) or use a clinical interview for establishing the presence of depressive disorders for participants.…”
Section: Discussioncontrasting
confidence: 76%
“…Concerning the effect that parental mental health has in sleep development in early childhood, and in relation to the perinatal period, depressed pregnant women seem to have newborns exhibiting higher levels of disrupted sleep. 35 Similarly, prenatal maternal anxiety and depression predict more sleep problems in toddlers aged 18–30 months, 36 and mothers with prenatal depression report more night awakenings in their one-year-old infants. 37 There is also evidence that both mother’s prenatal and early postpartum depression symptoms associate with the emergence of infant’s sleep problems.…”
Section: Methodsmentioning
confidence: 99%
“… Maternal depression and family disorganization were associated with sleep problems and anxiety in twins. Halal et al (2021) 36 Longitudinal 2222 Age=Newborns Age grouping: infancy. Actigraphy: sleep duration, night awakenings and sleep efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…In the first study we have hypothesized that maternal depression in the perinatal period would be associated with poor infant sleep, as results, we have observed that although mothers in the depressed group were more likely to report more night wakings in their children, objective data from actigraphy did not replicate this finding. Suggesting a dysfunctional cognition affecting the mother’s impression of her infant’s sleep 6 . The second study was a web-survey with data collected in the first months of the COVID 19 pandemics in Brazil, besides the findings of an increased prevalence of sleep problems in all age groups studied (children from 0 to 18 years and adults), the fact of having children with sleep disorders was a risk factor for parents worse sleep quality 7 .…”
mentioning
confidence: 99%